58.7k views
1 vote
Fiona is trying to prove that a pair of expressions are equivalent by using substitution. Which pair of expressions has the same value if she substitutes y = 3?

User JimiSweden
by
5.8k points

2 Answers

2 votes

Answer: 2y + 7 + y - 2 + y; 4y + 5

Step-by-step explanation: just did it

User Torindo
by
5.0k points
4 votes

Missing Part of the Question

  • 3 (4 - y) -7 ; 5 + 3y
  • 9 + y + 4y - 2 - 3y; -2y + 7
  • 5 + y - 2 - 6y + y; 8y + 3
  • 2y + 7 + y - 2 + y; 4y + 5

Answer:

  • 2y + 7 + y - 2 + y; 4y + 5

Explanation:

Given

y = 3

Required

Which pair of expression are equal

To get the pair of expression that are equal; we simply substitute 3 for y in each of the expressions

3 (4 - y) -7 and 5 + 3y

Substitute 3 for y in 3 (4 - y) -7

This gives 3(4 - 3) -7

= 3(1) - 7

= 3 - 7

= -4

Then Substitute 3 for y in 5 + 3y

This gives 5 + 3(3)

= 5 + 9

= 14

-4 and 14 are not equal

---------------------------------------------------------------------------------------

9 + y + 4y - 2 - 3y; -2y + 7

Substitute 3 for y in 9 + y + 4y - 2 - 3y

This gives 9 + 3 + 4(3) - 2 - 3(3)

= 9 + 3 + 12 - 2 - 9

= 13

Then Substitute 3 for y in -2y + 7

This gives -2(3) + 7

= -6 + 7

= 1

13 and 1 are not equal

---------------------------------------------------------------------------------------

5 + y - 2 - 6y + y; 8y + 3

Substitute 3 for y in 5 + y - 2 - 6y + y

This gives 5 + 3 - 2 - 6(3) + 3

= 5 + 3 - 2 - 18 + 3

= -9

Then Substitute 3 for y in 8y + 3

This gives 8(3) + 3

= 24 + 3

= 27

-9 and 27 are not equal

---------------------------------------------------------------------------------------

2y + 7 + y - 2 + y; 4y + 5

Substitute 3 for y in 2y + 7 + y - 2 + y

This gives 2(3) + 7 + 3 - 2 + 3

= 6 + 7 + 3 - 2 + 3

= 17

Then Substitute 3 for y in 4y + 5

This gives 4(3) + 5

= 12 + 5

= 17

17 and 17 are equal

Hence, Option D is correct

User Paul Bellora
by
4.4k points